Economic uncertainty and structural reforms: Evidence from stock market volatility - Alessandra Bonfiglioli; Rosario Crinò; Gino Alessandro Gancia (Quantitative Economics, 2022)
Does economic uncertainty promote the implementation of structural reforms? We answer this question using one of the most exhaustive cross-country panel data sets on reforms in six major areas and measuring economic uncertainty with stock market volatility. To identify causality, we exploit exogenous differential variation in countries' exposure to foreign volatility shocks due to predetermined and time-invariant bilateral characteristics. Across all specifications, we find that stock market volatility has a positive and significant effect on the adoption of reforms. This result is robust to the inclusion of a large number of controls, such as political variables, economic variables, crisis indicators, and a host of country, reform and time fixed effects, as well as across various approaches for accommodating heterogeneous trends and contemporaneous shocks. Overall, this evidence suggests that times of market turmoil, which are characterized by a high degree of uncertainty, may facilitate the implementation of reforms that would otherwise not pass.
Keywords: E02; E60; L51; 330; Liberalizations; stock market volatility; reforms; uncertainty